The study of wet adhesion behavior of the organic coating on mild steel substrate/ Mohd Fauzi Abdullah - Abdullah, Mohd Fauzi (2001)
Wet adhesion behavior of organic coating play an important role to determine the performance of organic coating. In this project, three types of non-pigmented organic coatings; alkyd, polyurethane and epoxy polyamide on mild steel substrate were studied. Water immersion and adhesion pull-tape test were carried out to determine the water uptake capacity and adhesion failure grade for each system. From the result obtained, it shows that as immersion time increase, the water uptake capacity will be increase but the failure grade will decrease. The rate of adhesion failure grade for alkyd was faster than epoxy polyamide and polyurethane. Average water uptake capacity for alkyd was the greatest, which was about 0.0029 kg/cm2 and average water uptake capacity for epoxy polyamide and polyurethane was only 0.0008 kg/cm2 and 0.0005 kg/cm2 , respectively.